Development and disparities in Maharashtra - a spatiotemporal analysis - Abdul Shaban; Bhole, L.M. (1999)
In this paper using 62 indicators (70 variables) and principal component analysis and distance statistics, an attempt has been made to measure the levels of development in various districts and regions in Maharashtra for the benchmark years 1972-73, 1982-83 and 1988-89. The study finds that regions of Vidarbha and Marathwada and the districts of Ratnagiri, Raigad, Dhule and Jalgaon have been the least developed both at sectoral and the aggregate levels of development. The study suggests an urgent need for reviewing the whole gamut of approaches towards development planning in the state and for emphasizing the development of agricultural sector and local resource-based labour-intensive industrialization in the under-developed districts/regions. - Reproduced
Keywords: Regional disparities - India - Maharashtra; regional disparities